ANALISIS STRATEGI PEMASARAN UNTUK MENINGKATKAN DAYA SAING PADA UMKM PABRIK PRODUKSI TAHU BANDUNG NR - Afriza Apriliana Fajri; Sungkono Sungkono; Dedi Mulyadi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This researcher is a Micro, Small and Medium Enterprises (SMEs) is an independent small business run by community groups or families. As an important part of the economy, especially in Indonesia, SMEs have an important role in encouraging the economic growth of the community in various sectors, both trade, agriculture, industry, services and other sectors. This research uses descriptive qualitative data with the methods used, namely library research, field research and interviews. The information was obtained directly from the UMKM tofu factory by conducting observations and surveys based on interviews with respondents. Secondary data is information obtained in ready-to-use forms such as library research, literature, the internet and various existing documents, to maintain the quality of Bandung NR Tofu products it is necessary to check/verify the quality of these products. which is one part that cannot be separated from production control. to evaluate the effectiveness of the marketing strategy of tofu factories in Karawang UMKM Bandung NR. This can include analyzing the advertising, distribution, pricing and branding strategies implemented by MSMEs at the Karawang Bandung NR Tofu Factory to identify marketing strategies to improve the competitiveness of the Karawang Bandung NR Tofu Factory. As with small and medium industrial enterprises in general, under the leadership of the Bandung NR MSME Tofu Factory penj.